Validation of diffusion MRI as a biomarker for efficacy using randomized phase III trial of bevacizumab with or without VB-111 in recurrent glioblastoma. Issue 1 (19th June 2021) - Ellingson, Benjamin M; Patel, Kunal; Wang, Chencai; Raymond, Catalina; Brenner, Andrew; de Groot, John F; Butowski, Nicholas A; Zach, Leor; Campian, Jian L; Schlossman, Jacob; Rizvi, Shan; Cohen, Yael C; et al.
Abstract: Background: Evidence from single and multicenter phase II trials have suggested diffusion MRI is a predictive imaging biomarker for survival benefit in recurrent glioblastoma (rGBM) treated with anti-VEGF therapy. The current study confirms these findings in a large, randomized phase III clinical trial. Methods: Patients with rGBM were enrolled in a phase III randomized (1:1), controlled trial (NCT02511405) to compare the efficacy and safety of bevacizumab (BV) versus BV in combination with ofranergene obadenovec (BV+VB-111), an anti-cancer viral therapy. In 170 patients with diffusion MRI available, pretreatment enhancing tumor volume and ADC histogram analysis were used to phenotype patients as having high (>1.24 µm 2 /ms) or low (<1.24 µm 2 /ms) ADCL, the mean value of the lower peak of the ADC histogram, within the contrast enhancing tumor. Results: Baseline tumor volume ( P = .3460) and ADCL ( P = .2143) did not differ between treatment arms. Univariate analysis showed patients with high ADCL had a significant survival advantage in all patients ( P = .0006), as well as BV ( P = .0159) and BV+VB-111 individually ( P = .0262). Multivariable Cox regression accounting for treatment arm, age, baseline tumor volume, and ADCL identified continuous measures of tumor volume ( P < .0001; HR = 1.0212) and ADCL phenotypes ( P = .0012; HR = 0.5574) as independent predictors of OS. Conclusion: Baseline diffusion MRI and tumor volume are independent imaging biomarkers of OS in rGBM treated with BV or BV+VB-111.